Understanding stenotic pulmonary arteries: Can computational fluid dynamics help us out?. (March 2022) - Conijn, Maartje; Krings, Gregor J.
Abstract: Background: Although pulmonary artery stenosis is common in congenital heart disease, not much is known about the hemodynamic impact. The effect of stenosis on flow, pressure and wall shear stress can be visualized with computational fluid dynamics. Objectives: The aim of this study was to evaluate whether computational fluid dynamics is able to predict flow distribution and pressure gradients in normal and stenotic pulmonary arteries. Methods: Three cases were selected. The cases included one normal anatomy and two geometries representing common patterns in pulmonary artery stenosis. The pulmonary bifurcation was reconstructed using 3D rotational angiography. On the inlet, a patient-specific transient mass flow curve was applied. Full patient-specific outlet boundary conditions were calculated and applied to the outlets of the models. Pressure and flow distribution outcomes were compared to cardiac catheterization and cardiovascular magnetic resonance imaging data respectively. Results: In all three cases, the computationally calculated flow distribution was equal to the values measured by magnetic resonance imaging. In one case the pressure in the main pulmonary artery was slightly overestimated by computational fluid dynamics with 7 mmHg. All other pressure outcomes were in complete agreement with the invasive pressure measurements. Conclusions: Pressure and flow distribution can be reliably predicted by computational fluid dynamics for normal and stenotic pulmonary arteries. The calculated values of pressure and flow distribution were in excellent agreement with the clinical values. This demonstrates the feasibility and reliability of this method for flow analysis in patients with stenotic pulmonary arteries. Highlights: Timing for treatment of pulmonary artery stenosis is often challenging. Numerical studies offer detailed information on hemodynamic parameters. The feasibility of patient-specific analysis with a compliant wall was analyzed. One normal and two common aberrant anatomies were investigated. The numerical results were in excellent agreement with the clinical data.